Sigeleng River Capacity Analysis, Kec. Brebes with HEC-RAS 4.1.0 - Yulia Feriska; Ahmad Izzuddin (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the cross-sectional capacity of the Sigulung river, Kec. Brebes based on hydrological and hydraulic analysis using the HEC-RAS 4.1.0 program. Hydrological calculations were carried out using rain data obtained from the Water Resources Management Office (PSDA) and Spatial Planning of Brebes Regency from 2009-2018. After calculating with several kinds of distribution methods, it is concluded that the appropriate distribution method used in this research is the log normal distribution. Then from the results of the distribution calculation, the distribution of rainfall at the return period is 2 years, 5 years, 10 years, 25 years, 50 years, and 100 years. There are several calculation methods in calculating the planned debit. The rational method was chosen because it produces the highest discharge compared to other calculation methods. This discharge will be input for hydrological analysis into the channel model in the HEC-RAS program which is then observed so that the output of the model obtains a cross-sectional and longitudinal cross-sectional view of the flow in the channel model and it is known at what time the channel discharge causes flooding. Based on the results of this study, it can be concluded that at the 25-year return period, the distribution of rainfall reaches 377.97 mm/hour with a planned discharge of 31.29 m3/second. And on this 25th anniversary, the cross-sectional capacity of the river can still accommodate it.